2002
DOI: 10.1007/s00134-001-1193-2
|View full text |Cite
|
Sign up to set email alerts
|

The combination of a heat and moisture exchanger and a Booster TM: a clinical and bacteriological evaluation over 96 h

Abstract: Adding the Booster to a hydrophobic HME improved the heat and water preservation of ventilatory gas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 28 publications
0
11
0
5
Order By: Relevance
“…Esses resultados 12 , que, em análise bacteriológica de 33 FTCU Hygrobac DAR, após 7 dias de uso, encontraram 20 FTCU esté-reis, entre os quais em 13 havia crescimento bacteriano insignificante. Thomachot et al 22 afirmam que o FTCU é impregnado com substâncias químicas que são meios pobres para o crescimento bacteriano.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Esses resultados 12 , que, em análise bacteriológica de 33 FTCU Hygrobac DAR, após 7 dias de uso, encontraram 20 FTCU esté-reis, entre os quais em 13 havia crescimento bacteriano insignificante. Thomachot et al 22 afirmam que o FTCU é impregnado com substâncias químicas que são meios pobres para o crescimento bacteriano.…”
Section: Discussionunclassified
“…No grupo estudado, realizou-se troca do FTCU a cada 24 horas, como recomendado pelos fabricantes. No entanto, vários estudos questionam a frequência da troca e seu uso prolongado por mais que 24 horas 22,23,25 . Djedaini et al 29 mostraram que as propriedades de filtro bacteriológico de um FTCU não foram modificadas com o uso por 48 horas e que a incidência de PAV foi idêntica entre indivíduos que usaram por 24 ou 48 horas.…”
Section: Discussionunclassified
“…12 Other active HMEs were tested and provided data in line with our results, with better hygrometric performance in comparison with the last generation of HMEs and with the possibility of maintaining adequate humidity when the active function is turned on or off. 25,26 It may be justified to seek systems that improve humidification performance with stable levels Ͼ 35 mg H 2 O/L. Indeed, there are very seldom endotracheal tube occlusions when humidification devices deliver inspiratory water content of ϳ30 mg H 2 O/L.…”
Section: Discussionmentioning
confidence: 99%
“…Capacitance hygrometers are commercially available, but the results provided may be difficult to interpret. 12 Indeed, variations between the minimum and maximum values of absolute humidity during inspiration with these hygrometers attain 10 mg H 2 O/L, limiting the interpretation of the results. 12 The differences between the tested HMEs' performances and the manufacturer's data also raise questions, as previous studies showed large differences in the opposite direction.…”
Section: See the Original Studies On Pages 1442 And 1449mentioning
confidence: 90%
“…12 Indeed, variations between the minimum and maximum values of absolute humidity during inspiration with these hygrometers attain 10 mg H 2 O/L, limiting the interpretation of the results. 12 The differences between the tested HMEs' performances and the manufacturer's data also raise questions, as previous studies showed large differences in the opposite direction. 9,10 Such reported high humidification performances of the tested HME with a very low internal volume (mean internal volume of 15 mL) seem difficult to attain.…”
Section: See the Original Studies On Pages 1442 And 1449mentioning
confidence: 90%